Overwintering parasitism is positively associated with population density in diapausing larvae of Chilo suppressalis - Xiao-long HUANG; Ting JIANG; Zhen-ping WU; Wan-na ZHANG; Hai-jun XIAO (Journal of Integrative Agriculture)
The suppression of overwintering population is essential in integrated pest management, but little is known about the biological mortality factors that reduce the overwintering density of Chilo suppressalis. Here, we examine the parasitism of overwintering larvae, and assume that key parasitoids strengthen the over-wintering population suppression. The natural parasitism incidence and related dominant parasitoids in overwintering larvae were investigated in two successive winters, in 2015–2016 and 2016–2017. Parasitism rates were also assessed in larvae collected from 15 different counties in 2016. The results showed that the parasitism incidence and dominant parasitoids in overwintering C. suppressalis larvae were significantly different for different sampling dates and sites. Overwintering larvae of C. suppressalis were mainly parasitized by Cotesia chilonis, and less often by Eriborus sinicus and Microgaster russata. Regression analysis indicated that the natural incidence of parasites in overwintering C. suppressalis larvae was positively correlated with the over-wintering larval density. The current work provides support for overwintering pest management strategies by showing the effectiveness of parasitoid communities as a bio-mortality factor for suppressing overwintering density.